U-Pb Zircon Ages, Geochemical and Sr-Nd-Hf Isotopic Compositions of Granitoids in Western Songpan-Garze Fold Belt： Petrogenesis and Implication for Tectonic Evolution - 蔡宏明 张宏飞 徐旺春 (Journal of earth science (Wuhan, China), 2009)
Granitoids are widespread in the Songpan-Garze （松潘-甘孜） fold belt, western China. These granitoids provide insight into regional tectono-magmatic events, basement nature and tectonic evolution. However, previous studies mainly focused on the eastern Songpan-Garze fold belt. In this article, five granitoid intrusions from the western Songpan-Garze fold belt have been studied. These intrusions are composed of quartz-diorite and granodiorite. Using LA-ICP-MS zircon dating method, the obtained magma crystallization ages are 219±2 Ma for the quartz-diorite and 216±5 Ma for the granodiorite. The ages, combined with regional geological analyses, show that they formed in a post-coilisional tectonic setting. The quartz-diorite and granodiorite display co-linear variation in their chemical compositions. REE compositions for both the quartz-diorite and granodiorite show strongly fractionated patterns with （La/Yb）N=5.02-18.34 and Eu/Eu^＊=0.44-0.89. The quartz-diorites have initial ^87Sr/^86Sr ratios （Isr） of 0.70929-0.71197 and εNd（t） values of -8.6 to -6.1 and the granodiorites have Isr values of 0.70549-0.70997 and εNd（t） values of -8.3 to -4.3. Zircon Hf isotopic data show εHr（t） values of -3.8 to ＋1.6 for the quartz-diorites and -1.2 to ＋3.0 for the granodiorites. Geochemical and Sr-Nd-Hf isotopic compositions indicate that the quartz-diorites and granodiorites have similar petrogenesis. We suggest that the magmas for the quartz-diorites and granodiorites were derived from partial melting of lower crustal mafic source, resulting from amphibole dehydration melting reaction. The probing of the magma source reveals that the western Songpan-Garze fold belt contains an unexposed continental basement, which is similar to the eastern Songpan-Garze fold belt. Geodynamically, it is proposed that a lithospheric delamination model can account for the magma generation for the quartz-diorites and granodiorites in the western Songpan-Garze fold belt.